2020
DOI: 10.1186/s12916-020-01744-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-malarial febrile illness: a systematic review of published aetiological studies and case reports from Africa, 1980–2015

Abstract: Background The availability of reliable point-of-care tests for malaria has heralded a paradigm shift in the management of febrile illnesses away from presumptive antimalarial therapy. In the absence of a definitive diagnosis, health care providers are more likely to prescribe empirical antimicrobials to those who test negative for malaria. To improve management and guide further test development, better understanding is needed of the true causative agents and their geographic variability. Methods A systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…In this new context, it should be recommended to formulate an alternative calculation of dengue risk indices in Africa. Moreover, particular attention should be drawn on febrile illnesses in West Africa as arboviral infections are often recorded or misdiagnosed as malaria [ 205 , 206 , 207 ]. Therefore, it should be important to “deconstruct malaria-industrial complex [ 24 , 208 ]” by performing additional tests to check the presence of an arbovirus among acute fever cases in inpatients and outpatients in the local hospitals [ 24 , 208 , 209 , 210 , 211 , 212 , 213 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this new context, it should be recommended to formulate an alternative calculation of dengue risk indices in Africa. Moreover, particular attention should be drawn on febrile illnesses in West Africa as arboviral infections are often recorded or misdiagnosed as malaria [ 205 , 206 , 207 ]. Therefore, it should be important to “deconstruct malaria-industrial complex [ 24 , 208 ]” by performing additional tests to check the presence of an arbovirus among acute fever cases in inpatients and outpatients in the local hospitals [ 24 , 208 , 209 , 210 , 211 , 212 , 213 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 4099 (2410 in Asia, 1065 in Africa, 624 in Latin America) met selection criteria. A wide diversity of pathogens and their distribution are described (see [5] in press, [7] in press, [10] in press).…”
Section: Introductionmentioning
confidence: 99%
“…Febrile illness mapping-much of the world without data and without evidencebased treatments Paul N. Newton 1,2,3,4* and Philippe J. Guerin 1,5…”
mentioning
confidence: 99%
“…Pneumonia, diarrhoea and fevers persist as frequent reasons for seeking healthcare in low- and middle-income countries, particularly among children [ 1 – 5 ]. Sub-Saharan Africa (SSA) bears a disproportionately high burden of morbidity and mortality due to such common infections [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is less frequently assessed at the syndrome level, as it can have a multitude of infectious causes and therefore requires broad diagnostics [ 1 , 17 ]. A recent systematic review identified Staphylococcus aureus , non-typhoidal Salmonella and Escherichia coli to be the most commonly reported bacterial causes, and arboviruses to be among the most common viral causes of AFDUC in SSA [ 5 ]. This review highlighted the lack of data from rural areas, which tends to be neglected by surveillance efforts.…”
Section: Introductionmentioning
confidence: 99%